2022
DOI: 10.21009/japa.0302.14
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Financial Distress, Debt Default, dan Profitabilitas Terhadap Opini Audit Going Concern

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh Profitabilitas (X1), Intensitas Aset Tetap (X2) dan Leverage (X3) terhadap Tax Avoidance. Variabel independen pada penelitian ini adalah Profitabilitas dengan indikator Return On Asset (ROA), Intensitas Aset Tetap dengan indikator IAT dan Leverage dengan indikator Debt Equity Ratio (DER). Variabel dependen pada penelitian ini menggunakan Tax Avoidance yang diukur dengan menggunakan indikator Cash Effective Tax Rate (CETR). Metode yang digunakan pada penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Therefore, educated people will more easily accept new ideas. [6] The results of the hypothesis test showed that among the 38 respondents who had children suffering from diarrhea (cases), there were still 10 respondents (26.3%) who had sufficient knowledge. This is because mothers who have toddlers suffering from diarrhea are not caused by the mother's lack of knowledge about diarrhea, but are caused by other factors, namely children who do not wash their hands before eating and factors that the food consumed by children is less hygienic, especially children's snacks outside the home.…”
Section: Knowledge Risk Factors For the Incidence Of Diarrhea In Todd...mentioning
confidence: 97%
“…Therefore, educated people will more easily accept new ideas. [6] The results of the hypothesis test showed that among the 38 respondents who had children suffering from diarrhea (cases), there were still 10 respondents (26.3%) who had sufficient knowledge. This is because mothers who have toddlers suffering from diarrhea are not caused by the mother's lack of knowledge about diarrhea, but are caused by other factors, namely children who do not wash their hands before eating and factors that the food consumed by children is less hygienic, especially children's snacks outside the home.…”
Section: Knowledge Risk Factors For the Incidence Of Diarrhea In Todd...mentioning
confidence: 97%